Advances and challenges in endoscopy training: A mixed methods study among endoscopy trainers in the Netherlands - Mousset, Robert A; Diemers, Agnes; de Vos tot Nederveen Cappel, Wouter H; Pierie, Jean-Pierre E.N.; Langers, Alexandra M.J.; Brand, Paul L.P. (Endoscopy International Open, 2024)
Background and study aims Variation between trainers in providing traditional gastrointestinal endoscopy training, in which residents learn endoscopy by doing under the supervision of endoscopy trainers, may cause differences in endoscopy competence between residents. In this study, we explored endoscopy trainers’ views on the current status and desired future best practices regarding endoscopy training.Methods This mixed-methods study comprised quantitative survey data collected from 158 endoscopy trainers working in 26 gastroenterology teaching hospitals in the Netherlands and semi-structured interviews with 15 gastroenterology residency (associate) program directors (PDs). Survey data were analyzed using descriptive statistics and interview results with thematic analysis.Results There was considerable variability in endoscopy training practices between teaching hospitals in the structure of endoscopy supervision, criteria used to determine the level of supervision, and participation of trainers in endoscopy teaching courses. Interview participants agreed that an endoscopy training supervisor requires several teaching strategies, highlighting the importance of formal education in endoscopy teaching. Interview participants perceived self-regulated learning strategies as essential for residents to learn endoscopy effectively. The perceived main barriers to effective supervision were a lack of time and heavy workload. Participants expressed the desire for more standardization in endoscopy training programs between teaching hospitals.Conclusions Considerable variability in endoscopy training practices between gastroenterology teaching hospitals was identified. Formal education on endoscopy teaching, promotion of self-regulated learning, and standardization of endoscopy training programs and supervision practices have the potential to improve future endoscopy training.
Keywords: Endoscopy Upper GI Tract; Endoscopy Lower GI Tract; Quality and logistical aspects; Training